INNOVATIVE STRATEGIES FOR ENHANCING THE PEDAGOGICAL COMPETENCE OF RUSSIAN LANGUAGE TEACHERS (Actaeducation, 2025)
The article discusses an important issue in higher education: the significance of innovative teaching and the role of educational innovation. It emphasizes that innovative teaching methods come to life and are implemented by educators, who act as agents of change. Human element plays a crucial role in adopting and spreading these innovations, as teachers not only put them into practice, but also improve and modernize them through their daily work. This dynamic process highlights the critical importance of teacher creativity and flexibility in driving educational progress.